The Impact of Responsiveness on Patient Satisfaction: Ensuring Healthy Lives and Well-Being Through Sustainable Development Goal 3 - Hidayat, Dinnisa Haura Zhafira; Mimanda, Yona; Maikel, Mahesa Paranadipa (The Journal of Indonesia Sustainable Development Planning, 2025)
Responsiveness involves emotional support, effective communication, and respect, essential to achieving Sustainable Development Goal 3. The SDG 3 aims to ensure healthy lives and promote well-being. Therefore, aligning the principles of SDG 3 with healthcare practices will create a better healthcare environment. This study examines the effect of responsiveness on patient satisfaction at the hemodialysis unit of Rumah Sakit Haji Jakarta using a quantitative cross-sectional design with primary data collection and simple regression analysis. Findings indicate that responsiveness significantly and positively affects patient satisfaction at the hemodialysis unit of Rumah Sakit Haji Jakarta. In essence, greater attentiveness and quicker responses from healthcare providers lead to higher patient satisfaction. This outcome highlights the importance of ensuring healthcare services, especially in critical care areas like hemodialysis. These findings offer valuable insights and serve as a guiding reference for healthcare providers to improve patient care quality and achieve overall patient satisfaction.